(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To determine the rate of urinary retention after vaginal delivery and evaluation some factors related to urinary retention after vaginal delivery at Da Nang Hospital For Women And Chidren. Methods: Cross-sectional study describing 673 women giving birth vaginally, at Da Nang Hospital For Women And Chidren from March 2018 to the end of September 2018. The pregnant women in the research group will be examined, interviewed, and refer to the medical records to record the variables according to the research questionnaire. Results: Women who are primigravida with postpartum urinary retention rate 6.6%, higher than 2.4% for multigravida who have postpartum urinary retention. In infants with a weight of ≥ 3500 grams, the prevalence of birth urinary retention was 16.7%, higher than that of women with babies <3500 grams with neonatal urinary retention (1.7%). The rate of postpartum urinary retention among women who had a baby with a head circumference ≥ 36 cm was 24.3% higher than for women with a head circumference <36 cm (3.6%). The rate of urinary retention in pregnant women: asisted vaginal delivery was 50.0%; time of labor in stage 1 lasted ≥ 12 hours was 13.0%; the duration of second stage labor was 16.4% prolonged, higher than the rate of urinary retention in the group of pregnant women: vaginal delivery (4.6%); period of labor for stage 1 <12 hours (2.1%); period of labor for stage 2 did not last long (3.3%). In the group of women who did not exercise early after giving birth, the rate of urinary retention was 37.5%, higher than this group of women with early movement after birth, 1.3%. Conclusion: The rate of urinary retention after vaginal delivery is 4.8%. Factors: giving birth in comparison, giving birth to a large baby with a gestational weight: ≥ 3500 grams, head circumference ≥36 cm, asisted vaginal delivery, long stage 1 labor, long stage 2 labor, early postpartum inactivity increases the risk of postpartum urinary retention